2019
DOI: 10.3102/0002831219872738
|View full text |Cite
|
Sign up to set email alerts
|

Building Consensus: Idea Brokerage in Teacher Policy Networks

Abstract: We show how policy makers converged to support similar reforms on a major educational issue: teacher effectiveness. Our study demonstrates the importance of idea brokers—actors that facilitate connections between preferences in policy networks and promote consensus around new policy ideas. Our study is based on analysis of testimony from 200 Congressional hearings from 2001 to 2015. We use discourse network analysis to examine network ties based on policy preferences expressed in hearings. We visualize policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…Educational foundations are influential advocates in the policy implementation process (Bushhouse & Mosely, 2018;Hess & Henig, 2015;Galey-Horn et al, 2019;Reckhow & Tomkins-Stange, 2015. Major foundations function as linkage actors across several educational contexts, advocating for specific policy ideas within a network of entities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Educational foundations are influential advocates in the policy implementation process (Bushhouse & Mosely, 2018;Hess & Henig, 2015;Galey-Horn et al, 2019;Reckhow & Tomkins-Stange, 2015. Major foundations function as linkage actors across several educational contexts, advocating for specific policy ideas within a network of entities.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a growing body of literature examining the policy engagements of K-12 philanthropists demonstrated that funders are building strategic relationships between educational leaders and decision-makers, investing in boundary-spanning intermediaries that can champion shared goals (Bushhouse & Mosley, 2018;Galey-Horn, Reckhow, Ferrare, & Jasny, 2019;Reckhow, 2013;Reckhow & Tomkins-Stange, 2015Quinn, Tompkins-Stange & Meyerson, 2014). In higher education, research demonstrates that intermediaries are influential knowledge brokers, interpreting and spreading information and goals across several postsecondary contexts (Gándara et al, 2017;Hammond, Adams, Rubin & Ness, 2020;Miller & Morphew, 2017;Ness, 2010;).…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to this work, we now have a robust research base to guide more advanced statistical analyses of policy networks in educational domains. Initial attempts have already begun to advance this agenda using techniques such as exponential random growth models (e.g., Galey-Horn et al, 2020), but substantial work remains. Readers are free to copy, display, distribute, and adapt this article, as long as the work is attributed to the author(s) and Education Policy Analysis Archives, the changes are identified, and the same license applies to the derivative work.…”
Section: Discussionmentioning
confidence: 99%
“…During periods of dynamic policy change, like Kingdon's (1984) policy windows, policy brokers may bridge institutional arrangements by facilitating informational processes through diffuse issue networks. Meanwhile, within coalitions, these actors serve as "idea brokers" that facilitate the symbolic and practical links between policy preferences in different discourse coalitions (Galey-Horn et al, 2020). Although discourse coalitions focus on one issue area at a time, there may be multiple justifications for supporting a policy (Leifeld, 2017).…”
Section: Policy Network Analysis: Key Definitions and Conceptsmentioning
confidence: 99%
See 1 more Smart Citation